2014
DOI: 10.1016/j.camwa.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Free surface lattice Boltzmann with enhanced bubble model

Abstract: This paper presents an enhancement to the free surface lattice Boltzmann method (FSLBM) for the simulation of bubbly flows including rupture and breakup of bubbles. The FSLBM uses a volume of fluid approach to reduce the problem of a liquid-gas two-phase flow to a single-phase free surface simulation. In bubbly flows compression effects leading to an increase or decrease of pressure in the suspended bubbles cannot be neglected. Therefore, the free surface simulation is augmented by a bubble model that supplies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Note that, in contrast to higher order schemes [13], the normal vector information is not considered here. Nevertheless, the model has been shown to perform well for many different free-surface scenarios [14,15] and also in the context of GPU implementations [16].…”
Section: Free Surface Modelmentioning
confidence: 99%
“…Note that, in contrast to higher order schemes [13], the normal vector information is not considered here. Nevertheless, the model has been shown to perform well for many different free-surface scenarios [14,15] and also in the context of GPU implementations [16].…”
Section: Free Surface Modelmentioning
confidence: 99%
“…[23][24][25] This model tracks the actual volume of such gas regions and the initial volume from the beginning of the simulation.…”
Section: Free Surface Lbm (Fslbm)mentioning
confidence: 99%
“…Different methodologies for the numerical modeling bubble dynamics in gas-liquid two-phase flow have been explored by the volume-of-fluid (VOF) method, 26,27 level set (LS) method, 28,29 and lattice Boltzmann method. 30,31 Sussman and Puckett 32 compared the coupled LS and VOF (CLSVOF) method with the LS method, the VOF method, and the boundary integral method and verified that this coupled method was superior to VOF or LS alone. Chenadec et al 33 indicated that the CLSVOF method could achieve a satisfactory mass conservation error despite the complex topology, which illustrated the ability of the proposed method to accurately compute realistic configurations.…”
Section: Introductionmentioning
confidence: 99%